2006
DOI: 10.1097/01.shk.0000223134.17877.ad
|View full text |Cite
|
Sign up to set email alerts
|

The INHIBITION OF LPS-INDUCED PRODUCTION OF INFLAMMATORY CYTOKINES BY HSP70 INVOLVES INACTIVATION OF THE NF-κB PATHWAY BUT NOT THE MAPK PATHWAYS

Abstract: The objective of this study was to evaluate the negative regulatory role of heat shock protein 70 (HSP70) on endotoxin-induced activation of inflammatory cytokine signaling pathways in a macrophage cell line. Our studies show that elevation of HSP70 either by activation of the heat shock response (HSR) or through forced expression of the hsp70.1 gene downregulates cytokine expression. Our experiments showed that activation of the HSR and HSP70 overexpression could inhibit LPS-mediated expression of the proinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
79
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 32 publications
12
79
1
Order By: Relevance
“…Indeed, ANXA1 has been shown to negatively regulate IL-6 expression through the modulation of MKP1 (Yang et al 2006), and HSP70 levels were also higher in WT cells expressing ANXA1 in our study, indicating that ANXA1 is required for HSP70 induction after heat. The role of HSP70 in reducing TNFα levels has previously been shown (Shi et al 2006;van der Bruggen et al 1999) and supports our postulation that in response to heat and LPS, ANXA1 increases HSP70 expression (mRNA and protein), which can increase MKP1 levels, which in turn inhibit ERK, p38, and more likely JNK activation, leading to low TNFα levels (Fig. 7).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Indeed, ANXA1 has been shown to negatively regulate IL-6 expression through the modulation of MKP1 (Yang et al 2006), and HSP70 levels were also higher in WT cells expressing ANXA1 in our study, indicating that ANXA1 is required for HSP70 induction after heat. The role of HSP70 in reducing TNFα levels has previously been shown (Shi et al 2006;van der Bruggen et al 1999) and supports our postulation that in response to heat and LPS, ANXA1 increases HSP70 expression (mRNA and protein), which can increase MKP1 levels, which in turn inhibit ERK, p38, and more likely JNK activation, leading to low TNFα levels (Fig. 7).…”
Section: Discussionsupporting
confidence: 73%
“…In the current study, we show that potent pro-inflammatory cytokines TNFα and IL-6 were downregulated upon heat and LPS treatment as compared to LPS treatment. This is similar to other studies on TNFα (Shi et al 2006), IL-12 (Li et al 2001), andIL-6 (Ensor et al 1994), but opposite to other reported cytokines such as MIP2 (Garekar et al 2006). This regulation of cytokine production by heat can be related to another protective phenomenon known as endotoxin tolerance (Biswas and Lopez-Collazo 2009).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This induction of HSP70 required the amino terminus of ING1b but not the PHD, PBR and NLS region (Feng et al, 2006). HSP70 is known to inhibit the NF-kB pathways (Ran et al, 2004;Shi et al, 2006). More recently, it has been shown that the C-terminal PHD of ING1 interacts with histone H3 trimethylated at Lys4 (H3K4me3).…”
Section: Functionmentioning
confidence: 99%